2017
DOI: 10.1016/j.gaitpost.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The degree of misjudgment between perceived and actual gait ability in older adults

Abstract: Successful execution of motor tasks requires an integration of the perception of one's physical abilities and the perception of the task itself. Physical and cognitive decline associated with ageing may lead to misjudgments of these perceived and actual abilities and possibly to errors that may lead to balance loss. We aimed to directly quantify the degree to which older adults misjudge their actual gait ability. Twenty-seven older adults participated and were instructed to walk on a narrow path projected on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…The second proposition that could explain the weak association between the strategy selected by participants and the actual ability to recover, is that older adults generally have an imprecise perception of their actual abilities in relation to the task at hand. This is in accordance with previous studies investigating the discrepancy between the perceived and actual step ability (Sakurai et al, 2013 , 2016 ; Kluft et al, 2016 , 2017 ), which found that approximately one-third of older adults either over-or underestimate their abilities, when explicitly asked for their perceived ability. However, in these studies, the perceived and actual ability measures were nevertheless significantly associated, in contrast with the present result.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The second proposition that could explain the weak association between the strategy selected by participants and the actual ability to recover, is that older adults generally have an imprecise perception of their actual abilities in relation to the task at hand. This is in accordance with previous studies investigating the discrepancy between the perceived and actual step ability (Sakurai et al, 2013 , 2016 ; Kluft et al, 2016 , 2017 ), which found that approximately one-third of older adults either over-or underestimate their abilities, when explicitly asked for their perceived ability. However, in these studies, the perceived and actual ability measures were nevertheless significantly associated, in contrast with the present result.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies compared the actual ability to perform tasks to judgements of one's ability to perform these tasks (Butler et al, 2015 ; Kluft et al, 2016 ). When crossing narrow planks, almost one-third of the participating older adults showed risky behavior (Butler et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we compared between the participant's clinical assessment and their own perception of walking ability, good agreement (kappa 0.702) was observed. Although this finding was consistent with a study by Aziz et al (2014), a recent work found a contrary result (Kluft et al 2017). Kluft et al reported that the actual performance of walking and self-perception among the elderly was different.…”
Section: Discussionsupporting
confidence: 92%
“…Cross-sectional data 25 for community dwelling older people, although not with PD, indicate that with composure, appropriate fear of falling can also be a benefit of falls. The fear reduces future falls risk by helping people, who commonly misjudge their actual gait ability at older ages, 26 not to overestimate their falls efficacy (ability to maintain their balance) amid their physical limitations. From this perspective, ‘falling is not an error, it is a skill’ 27 that experience of falling can develop to release the intrinsic capability of people to make change with which they feel at ease.…”
Section: Credomentioning
confidence: 99%